Graphene Liquid Cells Assembled through Loop‐Assisted Transfer Method and Located with Correlated Light‐Electron Microscopy. (3rd February 2020) - van Deursen, Pauline M. G.; Koning, Roman I.; Tudor, Viorica; Moradi, Mohammad‐Amin; Patterson, Joseph P.; Kros, Alexander; Sommerdijk, Nico A. J. M.; Koster, Abraham J.; Schneider, Grégory F.
Abstract: Graphene liquid cells (GLCs) for transmission electron microscopy (TEM) enable high‐resolution, real‐time imaging of dynamic processes in water. Large‐scale implementation, however, is prevented by major difficulties in reproducing GLC fabrication. Here, a high‐yield method is presented to fabricate GLCs under millimeter areas of continuous graphene, facilitating efficient GLC formation on a TEM grid. Additionally, GLCs are located on the grid using correlated light‐electron microscopy (CLEM), which reduces beam damage by limiting electron exposure time. CLEM allows the acquisition of reliable statistics and the investigation of the most common shapes of GLCs. In particular, a novel type of liquid cell is found, formed from only a single graphene sheet, greatly simplifying the fabrication process. The methods presented in this work—particularly the reproducibility and simplicity of fabrication—will enable future application of GLCs for high‐resolution dynamic imaging of biomolecular systems. Abstract : Graphene liquid cells are femtoliter pockets of water confined between two layers of graphene, allowing real‐time transmission electron microscopy on liquid, room‐temperature samples. Light electron microscopy is used to efficiently locate graphene liquid cells on a transmission electron microscopy grid, assembled through the reliable loop‐assisted transfer method for free‐standing graphene sheets.